Reconstruction of Neglected Peroneal Tendon Dislocation Associated With a Large Lateral Malleolar Avulsion Fragment: A Case Study. Issue 2 (26th June 2021) - Lynch-Wong, Matthew; Walls, Andrew; Wong-Chung, John
Abstract : Peroneal tendon dislocation not infrequently passes undiagnosed, even in the presence of a lateral malleolar avulsion fragment, which can be small or large. The surgical treatment of a symptomatic dislocation without a bony avulsion or with a small bony avulsion consists simply of incising the superior peroneal retinaculum and reattaching it to the posterolateral margin of the fibula. In case of a large bony avulsion, the superior peroneal retinaculum must be left intact and must not be incised. Instead, the periosteum overlying the acute fracture site or over the healed fracture site in a neglected case as presented herein, is incised and periosteal flaps elevated to gain surgical access and permit an imbricated reconstruction of the retinaculum. Level of Evidence: Diagnostic Level V. See Instructions for Authors for a complete description of levels of evidence.